2019
DOI: 10.1007/430_2019_42
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Metal Ions and DNA

Abstract: 84 years elapsed between the announcements of the Periodic Table and that of the DNA double helix in 1953, and the two have been combined in many ways since then. In this chapter an outline of the fundamentals of DNA structure leads into a range of examples showing how the natural magnesium and potassium ions found in nature can be substituted in a diversity of applications. The dynamic structures found in nature have been studied in the more controlled, but artificial environment of the DNA crystal using exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…S2). We also observed that ion transport classes were enriched in the transcriptome, and it is important to highlight that metal ions play a critical role in stabilizing conformations, especially in the double helix structure of DNA (Sta Cardin, 2019). Metal ions also play an important role in the MRN complex (Lee and Paull, 2005; Nicolette et al ., 2010).…”
Section: Resultsmentioning
confidence: 86%
“…S2). We also observed that ion transport classes were enriched in the transcriptome, and it is important to highlight that metal ions play a critical role in stabilizing conformations, especially in the double helix structure of DNA (Sta Cardin, 2019). Metal ions also play an important role in the MRN complex (Lee and Paull, 2005; Nicolette et al ., 2010).…”
Section: Resultsmentioning
confidence: 86%
“…The conformational differences between furanose rings in RNA and DNA may be a manifestation of polymeric structures because nucleosides and nucleotides may crystallize in either of these two conformations. However, the degree of hydration and metal-ion coordination can significantly affect the conformation of the furanose ring; e.g., A-DNA (75% relative humidity, sodium salt) exhibits a C3′- endo conformation, whereas B-DNA (95% humidity, lithium salt) favors the C2′- endo form . First, the puckering amplitude (τ m ) and phase angle of pseudorotation ( P ) were defined by Altona and Sundaralingam in 1972 when they introduced the concept of pseudorotation to describe the puckering motion of the furanose ring in nucleosides and nucleotides .…”
Section: Introductionmentioning
confidence: 99%